Implementing a Randomized Controlled Trial through a Community-Academia Partnered Participatory Research: Arte con Salud Research-Informed Intervention - Noboa-Ortega, Patricia; Figueroa-Cosme, Wanda I.; Feldman-Soler, Alana; Miranda-Díaz, Christine (Puerto Rico Health Sciences Journal, 2017)
Objective: “Arte con Salud” is an HIV/AIDS prevention intervention tailored for Puerto Rican women who have sex with men. The intervention curriculum was refined through a community-academic collaboration between Taller Salud, the UPRCayey Campus, and the UCC-School of Medicine, subsided in 2012-13 by PRCTRC. The collaboration has been crucial to validate the impact of using art as a tool to facilitate sexual negotiation skills and safer sexual practices among adult women have sex with men participating in HIV prevention education. Methods: This article describes the vision, valley, victory phases endured to establish a community-academia partnership based on the CPPR framework as an effective mean to implement a randomized controlled trial intervention (RCT). We also discuss the barriers, outcomes, and lessons learned from this partnership. Results: Some of the identified solutions include: setting goals to secure funding, regular meetings, and the inclusion of undergraduate level students to assist in the implementation of the intervention. These solutions helped to build trust among the community and academic partners. As a result of this collaboration, a total of 86 participants were enrolled and 5 competitive research grants have been submitted. Conclusion: The community-academic collaboration was essential in order to build a solid research infrastructure that addresses the complexities of HIV prevention education among groups of Puerto Rican women.